SEMANTIK KONTEKSTUAL ISTILAH JALUR DALAM BAHASA MELAYU RIAU DIALEK KUANTANSINGINGI (Contextual Semantic of Jalur Long Boat Term in Kuantansingingi Dialect of Riau Malay Language) - Raja Saleh (Balai Bahasa Sulawesi Selatan, 2015)
The researchs are based on some reasons, they are some words/terms of Riau Malay language of Kuantansingingi dialect have similarities to Indonesian language but differences in meaning, and some words/terms of RiauMalay language of Kuantansingingi dialect still do not have synonym in Indonesian language. Based on the problems mentioned, the research aims at 1) describing words/terms relating to jalur and 2) giving clear definition of words/terms relating to jalur in accordance with the context of its use. The data is collected using noting, interview technique, and library study. The data then is analyzed using contextual semantic meaning. Result of the study shows that semantic contextual meaning has explained well words/terms in Riau Malaylanguage of Kuantansingingi dialect and definite meaning of words/terms relating to jalur in accordance with context of its use. Besides that, the analysis also finds out some words that do not have synonym in Indonesia such of pondaRo, lone, ciRaRua?, tukang onjei. Words/terms of Riau Malay language of Kuantansingingi dialect that have different meaning and concept of Indonesian languages are candia?, upie, pancang, tolingo, puse? , lampei, tukang, concang, buku-buku, mouRui? , and moiRi?